EVALUASI IMPLEMENTASI PROGRAM PENGUATAN PENDIDIKAN KARAKTER DI SD MUHAMMADIYAH PANDES PROGRAM PLUS TAHUN AJARAN 2019/2020 - Andrianto, Andrianto; Suyitno, Suyitno (universitas Ahmad Dahlan, 2021)
This study aims to describe the achievements of the character education program in the implementation of Teaching and Learning Activities, extracurricular activities, and the implementation of the character education program at SD Muhammadiyah Pandes. This study uses the CIPP (Context, Input, Process, and Product) model as a tool for evaluation. The method used in this research is descriptive. Collecting data in the evaluation process, namely interviews, observation, document study, and questionnaires. The data analysis techniques used in this study were data reduction, data presentation, and conclusion drawing. Sources of data were obtained from school principals, homeroom teachers, educators/teachers, students in grades 4, 5, and 6 as well as 10 representatives of guardians from grades 4, 5, and 6. The results showed that the character education program has achieved excellent results. Implemented by school residents. Among them at the context stage, the average achievement is in the high category, at the input stage in the high category, at the process stage in the high category, and at the product stage in the high category. Overall the character education program has met the standard criteria. Overall the character education program has met the standard criteria, but there are several focuses that need to be improved including, 1) the principal to make a decree for the character education task team, 2) the teacher to remain committed and increase the application of character values in daily school activities, 3) Students carry out character education programs that are held at school well and participate actively, 4) Parents must continue to work together with the school and pay special attention to their children by fostering and educating through habitual behavior and good behavior in everyday life.